BS EN ISO 52032. Energy performance of buildings. Method for calculation of system energy requirements and system efficiencies. Space distribution systems (DHW, heating and cooling), Module M3-6, M4-6, M8-6. (28th January 2020) - British Standards Institution,
No abstract available